Quercetin Preserves Oral Cavity Health by Mitigating Inflammation and Microbial Dysbiosis - Mooney, Erin C.; Holden, Sara E.; Xia, Xia-Juan; Li, Yajie; Jiang, Min; Banson, Camille N.; Zhu, Bin; Sahingur, Sinem Esra (Frontiers in Immunology, 2021)
Failure to attenuate inflammation coupled with consequent microbiota changes drives the development of bone-destructive periodontitis. Quercetin, a plant-derived polyphenolic flavonoid, has been linked with health benefits in both humans and animals. Using a systematic approach, we investigated the effect of orally delivered Quercetin on host inflammatory response, oral microbial composition and periodontal disease phenotype. In vivo, quercetin supplementation diminished gingival cytokine expression, inflammatory cell infiltrate and alveolar bone loss. Microbiome analyses revealed a healthier oral microbial composition in Quercetin-treated versus vehicle-treated group characterized by reduction in the number of pathogenic species including Enterococcus, Neisseria and Pseudomonas and increase in the number of non-pathogenic Streptococcus sp. and bacterial diversity. In vitro, Quercetin diminished inflammatory cytokine production through modulating NF-κB activity in human macrophages following challenge with oral bacteria and lipopolysaccharide. Collectively, our findings reveal that Quercetin supplement instigates a balanced periodontal tissue homeostasis through limiting inflammation and fostering an oral cavity microenvironment conducive of symbiotic microbiota associated with health. This proof of concept study provides key evidence for translational studies to improve overall health.